Quality of life analysis in ostomized colorectal cancer patients - Kimura,Cristilene Akiko (2013)
INTRODUCTION: the oncological patient submitted to ostomy faces multiple losses which affect their quality of life. OBJECTIVE: assess quality of life in ostomized patients due to colorectal cancer, regarding the physical, psychological, social and environmental relationships, treated at the Ostomy Program of the Health Department of Distrito Federal, Brazil. METHODS: epidemiological-based, analytical, cross-sectional and descriptive study. The sample consisted of 54 patients enrolled in the Ostomy Program of the Health Department of Distrito Federal - Brazil. The WHOQOL-BREF questionnaire was used to evaluate quality of life. Data was analyzed by Microsoft (r) Office Excel 2010 and SPSS 20.0. RESULTS: the Physical, Social and Environmental aspects were correlated to the mean score, resulting in statistical significance (p<0.0001). The item "Positive feelings" in the Psychological Domain was the only one that did not achieve statistical significance. CONCLUSION: the results demonstrate that the care of cancer patients with ostomies should focus on the technical-scientific, political and socio-educational actions, to allow a multidisciplinary team to recognize health as a right for all, working to guarantee the health care process.